Neurodegeneration and Alzheimer's disease (AD). What Can Proteomics Tell Us About the Alzheimer's Brain? - Moya-Alvarado, Guillermo (Mol Cell Proteomics, 2016)
Neurodegenerative diseases, such as Alzheimer′s diseases (AD), are becoming more prevalent as the population ages. However, the mechanisms that lead to synapse destabilization and neuron death remain elusive. The advent of proteomics has allowed for high-throughput screening methods to search for biomarkers that could lead to early diagnosis and treatment and to identify alterations in the cellular proteome that could provide insight into disease etiology and possible treatment avenues. In this review, we have concentrated mainly on the findings that are related to how and whether proteomics studies have contributed to two aspects of AD research, the development of biomarkers for clinical diagnostics, and the recognition of proteins that can help elucidate the pathways leading to AD brain pathology. As a result of these studies, several candidate cerebrospinal fluid biomarkers are now available for further validation in different AD cohorts. Studies in AD brain and AD transgenic models support the notion that oxidative damage results in the alterations of metabolic enzymes and that mitochondrial dysfunction is central to AD neuropathology.